Некоторые методологические принципы создания функциональных покрытий для режущего инструмента - Верещака, А. С.; Верещака, А. А. (НТУ "ХПИ", 2010)
В статье представлены методологические принципы создания функциональных покрытий для режущего инструмента. Разработанная высокопрочная композиционная керамика с наноструктурированным покрытием позволяет повысить стойкость режущего инструмента до 2-3 раз по сравнению со стойкостью инструмента стандартного типа.

Some questions of creation methodology of functional coatings for an cutting tools are observed. On the basis of the coating concept as intermediate technological medium between the working and cutting tool materials it is proved application of the multilayer architecture of a coating and the basic demands to its elements are formulated. The basic requirements to elements of the multilayer coating are formulated and the technique of sampling for coating compositions, structure and properties for various machining conditions is presented. Instances of implementation of the developed scientific positions are shown.
Keywords: композиционная керамика; наноструктурированные покрытия; высокопрочная композиционная керамика; фильтруемое вакуумно-дуговое осаждение; многослойно-композиционное покрытие; functional coatings; cutting tools; multilayer architecture